2014
DOI: 10.1007/s40204-014-0028-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effects of silver–zirconia composite coatings using pulsed laser deposition onto 316L SS for bio implants

Abstract: Bacterial invasion on biomedical implants is a challenging task for long-term and permanent implant fixations. Prevention of initial bacterial adherence on metallic implants is an important concern to avoid extracellular matrix (biofilm) secretion from bacteria that is resistant to antibacterial agents. In order to overcome this defect, recently, surface coatings such as zirconia (ZrO2) with higher smoothness have been shown to improve implants durability. In the present study, pulsed laser deposition (PLD) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…aureus and fungus due the different structure and chemical composition of the outer membrane of both types of bacteria regarding their charge and chemical moieties. Another study showed that Ag–ZrO 2 composite coatings show superior antibacterial activity against Gram‐negative E. coli and Gram‐positive S. aureus strains compared with a ZrO 2 coating . It was found that the SnO 2 (F) photocatalyst progressively damaged the bacterial cell membrane and had a considerable photocatalytic inactivation effect …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus and fungus due the different structure and chemical composition of the outer membrane of both types of bacteria regarding their charge and chemical moieties. Another study showed that Ag–ZrO 2 composite coatings show superior antibacterial activity against Gram‐negative E. coli and Gram‐positive S. aureus strains compared with a ZrO 2 coating . It was found that the SnO 2 (F) photocatalyst progressively damaged the bacterial cell membrane and had a considerable photocatalytic inactivation effect …”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that Ag-ZrO 2 composite coatings show superior antibacterial activity against Gram-negative E. coli and Gram-positive S. aureus strains compared with a ZrO 2 coating. [25] It was found that the SnO 2 (F) photocatalyst progressively damaged the bacterial cell membrane and had a considerable photocatalytic inactivation effect. [26] We can accept that the mechanism of antibacterial activity of metal oxides is due to their interaction with highly reactive oxygen species, which would result in damage to the outer membrane or inside the cells of the bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…A comparative study was done on the deposition of ZrO 2 and silver (Ag)–ZrO 2 composite coatings by the pulsed laser deposition (PLD) technique onto 316L stainless steel (316L SS) against the activity of bacteria. It showed that compared to ZrO 2 coatings, Ag–ZrO 2 composite coatings had better results against Escherichia coli and Staphylococcus aureus strains . Another study with the reactive magnetron co‐sputtering technique on implants demonstrated less bacterial attachment, hemocompatibility, and anticorrosion activities of TiZrN coating on 316L SS against S. aureus and E. coli .…”
Section: Biofilms In Different Componentsmentioning
confidence: 99%
“…However, these appear to be of limited use in orthodontics, as they can cause enamel discoloration and cosmetic treatment results. The other approach to reducing the failure rate due to dental caries has been to modify the arches or brackets with coatings such as TiO 2 nanoparticles doped with nitrogen [ 38 , 40 ] or Ag–Zr nanocomposite coatings [ 38 , 41 ].…”
Section: Prevention Of Dental Caries and Control Of Oral Biofilmmentioning
confidence: 99%